Advocating for Patients: Honoring Professional Trust. (26th October 2016) - Galuska, Lee
Abstract: Perioperative nurse leaders create conditions for nurses in all health care settings that allow them to advocate for patients when they are unable to advocate for themselves; these conditions also enable nurses to enter into therapeutic relationships with patients and their families and establish trust. The nursing leadership practices that facilitate this advocacy include promoting continuity of care and patient relationships; helping to ensure practice environments support teamwork and collaboration; providing behavioral expectations for communication and conflict management; and supporting practices that promote self‐care and ongoing professional development, flexibility, creativity, and innovation to meet patient care needs. A comprehensive professional practice model provides a framework for nurses to practice more fully and to skillfully care and successfully advocate for patients.